Causal Learning Across Culture and Socioeconomic Status. Issue 3 (23rd August 2017) - Wente, Adrienne O.; Kimura, Katherine; Walker, Caren M.; Banerjee, Nirajana; Fernández Flecha, María; MacDonald, Bridget; Lucas, Christopher; Gopnik, Alison
Abstract : Extensive research has explored the ability of young children to learn about the causal structure of the world from patterns of evidence. These studies, however, have been conducted with middle‐class samples from North America and Europe. In the present study, low‐income Peruvian 4‐ and 5‐year‐olds and adults, low‐income U.S. 4‐ and 5‐year‐olds in Head Start programs, and middle‐class children from the United States participated in a causal learning task ( N  = 435). Consistent with previous studies, children learned both specific causal relations and more abstract causal principles across culture and socioeconomic status (SES). The Peruvian children and adults generally performed like middle‐class U.S. children and adults, but the low‐SES U.S. children showed some differences.